PENGARUH SOCIAL MEDIA MARKETING, CUSTOMER RELATIONSHIP MANAGEMENT DAN SERVICE QUALITY TERHADAP PATIENT SATISFACTION PADA INSTASKIN BALI - Kurniawan, Ida Bagus; Ardana, I Made Dwi Wira; Bernardus, I Nyoman (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
Instaskin Bali Clinic is a clinic that provides skincare services, genitals, and esthetics located in Denpasar, Bali. To date, Instaskin Bali Clinic has been committed to continuing to improve the quality of service for patients. With the hard work, this clinic takes several steps, including building good relationships with patients, improved the qualitys of services when patients visit, and updating clinic information via social media. This study is conducted to analyzed influenced of Social Media Marketing, Customer Relationships Management, and Service Quality on Patients Satisfaction in Instaskin Bali. The survey was dispersed online to 100 respondents who are patients Instaskin Bali. This research using multiple linear regression. The result says that’s Social Media Marketing, Customer Relationship Management and Service Quality partially influence to Patient Satisfaction. When tested together all variables X have an influence to variable Y where percentage 84.2% and 16.8% from other variables not examined in this study.